2006
DOI: 10.1159/000097695
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and Polymorphisms in Genes Affecting Haemostasis Components in Children with Thromboembolic Events

Abstract: The distribution of mutations/polymorphisms in genes affecting haemostasis [factor V Leiden (FVL), FV H1298R (FVR2), FII 20210A, b-Fib 455G→A, FXIII V34L, PAI-1 4G, HPA-1b] among 141 children with thrombosis at various sites and 103 controls was compared. Additionally, the carriage of these mutations/polymorphisms was associated with the levels of their corresponding proteins in thrombosed children. Thrombosis was more frequent in boys (p = 0.021). No studied mutation/polymorphism was found to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The role of elevated PAI concentrations and PAI-4G/ 4G genotype in thrombosis is currently being investigated [15]. Though an elevation in PAI-1 concentration is thought to incur a moderate thrombotic risk, the presence of the 4G/4G genotype is not clearly associated with thrombosis in children [16][17][18]. In our patients, we did not screen for the presence of 4G/4 G genotype but elected to test the PAI-1 activity as the PAI-1 concentrations are affected by other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The role of elevated PAI concentrations and PAI-4G/ 4G genotype in thrombosis is currently being investigated [15]. Though an elevation in PAI-1 concentration is thought to incur a moderate thrombotic risk, the presence of the 4G/4G genotype is not clearly associated with thrombosis in children [16][17][18]. In our patients, we did not screen for the presence of 4G/4 G genotype but elected to test the PAI-1 activity as the PAI-1 concentrations are affected by other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although higher FXIII activity was found for 34Leu carriers, 140 the Val34Leu polymorphism was not associated with susceptibility to venous thrombosis or ischemic stroke. 100,103,140,141 In two large studies, Leu/Leu genotype 142 and 34Leu allele 19 revealed a protective effect on venous thrombosis.…”
Section: Factor XIIImentioning
confidence: 99%
“…8 In adult patients with severe pneumonia, the 4G allele has also been associated with increased susceptibility to community-acquired pneumonia, increased mortality, and fewer ventilator-free days. 98,99 The SERPINE1 4G/5G polymorphism has already been extensively studied in venous thrombosis 18,90,100,101 and ischemic stroke. [102][103][104][105][106] Most studies, including both small and large groups of patients, failed to associate this polymorphism with disease.…”
Section: Plasminogen Activator Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation